Penetapan Kadar Flavonoid, Kadar Tannin serta Profil Fitokimia Ekstrak Etanol 96% Biji Alpukat (Persea Americana Mill) - Putri, Siti Maida; Tri R., H, Marybeth (IAI Nasional Laa Roiba Bogor, 2024)
One of the plants in Indonesia that can be used as traditional medicine is avocado seeds (Persea American Mill). Avocado seeds are known to contain flavonoid compounds, phenols and tannins. Flavonoids are one of the compounds that can ward off free radicals that cause degenerative diseases.The flavonoid compounds in avocado seeds are taken by extracting avocado seeds. Avocado seeds were extracted using the maceration method using 96% ethanol solvent. Determination of flavonoid levels begins with qualitative phytochemical analysis, then flavonoid levels are measured using the UV-Visible spectrophotometer method with the reference standard quercetin. The extract obtained was subjected to qualitative phytochemical analysis by testing phenolics, flavonoids and tannins using reagents appropriate to the test parameters. Meanwhile, quantitative phytochemical analysis of flavonoid compounds uses the UV-Visible Spectrophotometry method. The results of qualitative phytochemical analysis show that avocado seeds contain positive flavonoid compounds, phenols and tannins. Based on the results of quantitative phytochemical analysis using visible UV spectrophotometry, it shows that the level of flavonoid compounds in the ethanol extract of avocado seeds (Persea American Mill), which was read at the maximum wave obtained, namely 435 nm, was 0.2124%.